Phenotypic spectrum and antialbuminuric response to angiotensin converting enzyme inhibitor and angiotensin receptor blocker therapy in pediatric Dent disease - Deng, Haiyue (Mol Genet Genomic Med, 2020)
BACKGROUND: To characterize the phenotypic spectrum and assess the antialbuminuric response to angiotensin converting enzyme (ACE) inhibitor and/or angiotensin receptor blocker (ARB) therapy in a cohort of children with Dent disease. METHODS: The patients’ clinical findings, renal biopsy results, genetic and follow‐up data were analyzed retrospectively. Mutations in CLCN5 or OCRL were detected by next‐generation sequencing or Sanger sequencing. RESULTS: Of 31 Dent disease boys, 24 carried CLCN5 and 7 carried OCRL mutations. Low molecular weight proteinuria and albuminuria were detected in all cases. Nephrotic‐range proteinuria and severe albuminuria were identified in 52% and 62% of cases, respectively; by 7 years of age, 6 patients had hematuria and nephrotic‐range proteinuria, and 7 patients had hematuria and moderate to severe albuminuria. In addition to disease‐related renal features, patients with Dent‐1 disease also presented with congenital cataract (1/9) and developmental delay (2/7). Seventeen of 31 patients underwent renal biopsy. Glomerular changes included mild glomerular lesions, mesangial proliferative glomerulonephritis and focal segmental glomerular sclerosis. Thirteen of the 31 patients had follow‐up records and received ACE inhibitor and/or ARB treatment for more than 3 months. After a median 1.7 (range 0.3–8.5) years of treatment, a reduction in the urinary microalbumin‐to‐creatinine ratio was observed in 54% of children. CONCLUSIONS: Hematuria with nephrotic‐range proteinuria or moderate to severe albuminuria was common in Dent disease patients. Extrarenal manifestations were observed in Dent‐1 patients, which extends the phenotypic spectrum. In addition, ACE inhibitors and ARBs are well tolerated, and they are partially effective in controlling albuminuria.